Environmental noise pollution noise mapping, public health, and policy - Murphy, Enda (Elsevier, 2014)
"This book offers an introduction to the concept of environmental noise pollution. In doing so, it provides the contextual background for understanding concerns around environmental noise pollution. This includes elucidating variations in the definition of noise vis-áa-vis environmental noise. It also provides a reflective introduction to key debates and challenges in the environmental noise pollution area from issues around the historical dimension of noise pollution in cities to modern challenges facing policymakers in an increasingly urbanised society"-- Provided by publisher.
Keywords: hluk -- environmentální aspekty; hluk -- zdravotní aspekty; noise -- environmental aspects; noise -- health aspects; elektronické knihy; electronic books